1975
DOI: 10.1007/bf00490073
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical discrimination between catalases and peroxidases using diaminobenzidine

Abstract: The influence on diaminobenzidine staining of four variables: prefixation in aldehyde, temperature and pH of incubation, and H2O2 concentration, was investigated in catalase-, as well as in peroxydase-containing material. Catalase from five different sources and five types of peroxidase were examined. It is concluded: (a) when cells are incubated without prior fixation, in a DAB medium at room temperature and pH 7.3 with 0.003% H2O2, peroxidases produce a visible cytochemical stain, while catalases do not; (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(53 citation statements)
references
References 120 publications
0
52
0
1
Order By: Relevance
“…4). Significant reaction products were only obtained for mitochondrial cristae, most likely caused by an intramitochondrial peroxidase reaction (39). Notably, the DAB-positive organelles adjoined to vacuoles as described for the N. crassa slime mutant were never observed, even when serial ultrathin sections of a cell were inspected (see Fig.…”
Section: Intracellular Distribution Of Catalase Activitymentioning
confidence: 89%
“…4). Significant reaction products were only obtained for mitochondrial cristae, most likely caused by an intramitochondrial peroxidase reaction (39). Notably, the DAB-positive organelles adjoined to vacuoles as described for the N. crassa slime mutant were never observed, even when serial ultrathin sections of a cell were inspected (see Fig.…”
Section: Intracellular Distribution Of Catalase Activitymentioning
confidence: 89%
“…However, this appears to be due to suboptimal preservation of this enzyme under the conditions used. With an adapted methodology (24,29), these bodies become positive. Catalase-positive peroxisomes have already been described by several authors in other yeast species and under other growth conditions (16,22,25,26,28,33,34,39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the following variation in the fixation procedure was used for the localization of catalase: the 7.5-,um sections were fixed for 24 h in a 4% formol solution containing 1% CaCl2 (29). After a 1-min wash, the sections were incubated in the catalase medium as described below.…”
mentioning
confidence: 99%
“…4, 9), and that in the epithelial cells of the other tissues, such as lacrimal glands and salivary glands (8,20), also produces only a little or no visible cytochemical stain. With respect to the influence of H2O2 on peroxidases, Roels et al (16) have reported the inhibition of peroxidase activity by higher concentration of H2O2. In our experimental conditions, 0.005% H2O2 for the localization of peroxidase yielded the same staining intensity as 0.01% after the technique of The localization pattern of peroxidase-positive cells in the germ-free adult rats was identical to that in the conventional.…”
Section: Discussionmentioning
confidence: 99%